The Little Book of Big Customer Satisfaction Measurement. - Rao, Ajit (SAGE Publications, 2013)
This book explains the principles of customer satisfaction in a brief yet powerful manner. It will help readers build relevant and actionable customer satisfaction programmes for their organization.